Animal Abuse Proclivity Among Women: Exploring Callousness, Sadism, and Psychopathy Traits. (2nd January 2022) - Ireland, Jane L.; Birch, Philip; Lewis, Michael; Mian, Ushna; Ireland, Carol A.
ABSTRACT: Two studies examining adult women are presented. The first ( n  = 162) examined the relationship between proclivity (i.e., interest in, predisposition) to abuse animals and the link to aggression motivation, with psychopathy traits, sadism, and general maladaptive personality explored. The second study ( n  = 159) extended to focus on callous-unemotional traits. We predicted that proclivity to abuse would be associated with increased proactive aggression, with the former also associated with higher levels of psychopathy, sadism, and callousness. These traits were expected to mediate the relationship between proclivity to abuse and aggression. Results confirmed that between one- to two-thirds of women reported at least some proclivity to abuse animals. An association between proclivity and proactive aggression was demonstrated, with callousness-uncaring and sadism representing important traits to account for. Results are discussed with attention to the implications for developing a theoretical understanding of the proclivity to abuse animals.